2014
DOI: 10.12697/poa.2014.23.2.11
|View full text |Cite
|
Sign up to set email alerts
|

The Körmend growth study 1968 and 2008: Somatotypes of the boys

Abstract: SThe Körmend Growth Study, a series of cross-sectional anthropological surveys, repeated in every 10 years since 1958, was among the firsts to demonstrate the existence of secular trends in the growth and the maturation of children. In this paper the authors give an overview on the physique of the Körmend boys based on the Körmend Growth Study. Somatotype (physique; defined according to the Heath-Carter anthropometric method) of 6-18-year-old boys, measured in 1968 (K-68) and 2008 (K-008), was analyzed and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…In Hungary, the secular trend is thoroughly studied, even since the second half of the nineteenth century we have comparative data on the stature of the recruits [20,21], in university students, and also in athletic and non-athletic samples of youth [13,15,[22][23][24][25][26][27][28][29][30][31][32][33][34]. Two nationwide studies also showed us the changes of the growth trends [25,35]. The anthropometric studies over Hungary demonstrate the regional differences in growth and developmental patterns and in the magnitude of body measurements' trend [36][37].…”
Section: Introductionmentioning
confidence: 99%
“…In Hungary, the secular trend is thoroughly studied, even since the second half of the nineteenth century we have comparative data on the stature of the recruits [20,21], in university students, and also in athletic and non-athletic samples of youth [13,15,[22][23][24][25][26][27][28][29][30][31][32][33][34]. Two nationwide studies also showed us the changes of the growth trends [25,35]. The anthropometric studies over Hungary demonstrate the regional differences in growth and developmental patterns and in the magnitude of body measurements' trend [36][37].…”
Section: Introductionmentioning
confidence: 99%